Genesis 37 and 39 in the Early Syriac Tradition - Heal, Kristian S. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2023., 2023)
The Syriac reception of the story of Joseph offers an unprecedented glimpse into late antique Syriac literary culture. The story inspired a diverse body of texts, written in prose, narrative poetry, dialogue poetry, and metrical homilies, including the greatest narrative poem written in Syriac. These texts explore and retell the story of Joseph with a combination of exegetical imagination, playful creativity, and a relentless focus on the exemplary virtues of the patriarch. Read through a typological lens, this study shows how the story also became an important locus of Christian-Jewish polemic.